The Impact of Down Syndrome on Perioperative Anesthetic Management and Outcomes in Infants Undergoing Isolated Ventricular Septal Defect Closure - Serife Ozalp; Funda Gumus Ozcan (Diagnostics)
Background: Down syndrome (DS) is associated with unique anatomical and physiological characteristics that complicate the perioperative management of infants undergoing cardiac surgery. While ventricular septal defect (VSD) repair is commonly performed in this population, detailed data comparing perioperative outcomes in DS versus non-syndromic infants remain limited. Methods: This retrospective matched study analysed 100 infants (50 with DS and 50 without DS) who underwent isolated VSD closure between January 2021 and January 2025. Patients were matched by age and surgical date. Intraoperative anesthetic management, complications, postoperative outcomes, and mortality were compared between groups. Results: DS patients had lower age, weight, and height at surgery. They required significantly smaller endotracheal tube sizes, more intubation and vascular access attempts. The DS group had significantly lower rates of extubation in the operating room and experienced longer durations of mechanical ventilation and ICU stay. However, no significant differences were observed in total hospital stay or mortality between groups. Conclusions: Although DS infants present with increased anesthetic complexity and respiratory challenges, they do not exhibit higher surgical mortality following isolated VSD closure. Tailored perioperative strategies may improve respiratory outcomes in this high-risk group.